Employment and Skills in Finland - Pareliussen, Jon (OECD Economics Department Working Papers, 2016)
Employment fosters equity and economic inclusiveness because those out of work face the highest risk of poverty, and it generates the tax receipts on which the social safety net depends. Further enhancing education and life-long learning would lower hurdles to employment, which are high for the low-skilled. Policies to speed up tertiary graduation, improve work incentives and activation of the unemployed and postpone labour market exit are necessary to bring the employment rate closer to the level of other Nordics. Easing employment regulations and allowing more flexible wage setting would increase both employment and productivity. This working paper relates to the 2016 OECD Economic Survey of Finland (www.oecd.org/eco/surveys/economic-survey-finland.htm)